Imagery-induced relaxation as a psychological intervention tool in children with cancer - Taib, Mai Nurul Ashikin; Nasir, Ariffin; Othman, Azizah; Sharifudin, Mohd Ariff (2014)
Background: Psychologically-directed therapies have been shown to be effective in reducing stress and enhance well-being. The objective of this study was to develop an imagery-induced relaxation (IIR) audio in Bahasa Malaysia as an interventional psychological tool and pilot test it to a group of paediatric oncology patients in the hope to improve the patient’s well-being as a whole. Methodology: 18 cancer children were recruited for this study. The imagery-induced relaxation (IIR) tool was developed where face and content validation were obtained via reports from experts. An interventional study was conducted to look at the effect of the IIR audio in modifying the physiological and mood indicators as well as the quality of life score in children with cancer. The quality of life scores were measured using the PedsQL 4.0 Generic Core Scale and PedsQL 3.0 Cancer Module. The physiological relaxation indicators were measured using a self-contructed rating scale. Mood and pain were measured using the Ottawa-Georgia Mood Faces Scale and Wong-Baker Pain analogue scale. Multiple comparisons between the pre and post intervention was analysed with Friedman test with Bonferroni correction to detect the differences in indicators score across over time. Results: There was no significant difference in the quality of life score. However, the differences in all the physiological indicators; calmness of heart beats (χ2 (4) = 21.02, p= <0.001), feeling of comfortness (χ2 (4) = 24.80 , p= <0.001), perception of no pain (χ2 (4) = 16.20, p= 0.003) and feeling of perceived strength (χ2 = 17.50 p= 0.002), mood; stress (χ2 (4) = 17.731, p= 0.001), sad (χ2 (4) = 13.522, p= 0.009), anxiety (χ2 (4) = 12.290, p= 0.015) and anger (χ2 = 16.905, p= 0.002) and pain (χ2 (4) = 9.882, p= 0.042) between time (pre and post intervention) were significant. The mean rank for all the indicators showed improvement with time indicating better physiological response, mood and less pain. Conclusion: This study has successfully become a pioneer in developing an imagery induced audio in Bahasa Malaysia, which is feasible and enjoyable by children. The imagery-induced relaxation audio has also shown potential benefit in inducing positive effects on physiological indicators of relaxation, mood and pain in cancer children. Future randomized controlled trials are needed to confirm our findings.